Situation Report: Albania, 22 January 1962 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Albanian Delegation Leaves China Delegation Arrives in Rangoon Albanian Trade Delegation to Pyongyang Albanian on Trial in Belgrade Hoxha Greets the US CP Albanian Envoy Attends the Warsaw Meeting Albanian Theoretical Journal Attacks Khrushchev Albanian Solidarity with Cuba